Retracted: Implications of Settlement Expansion on the Availability of Green Open Space in Medan Johor District - Syarif Hidayatullah; Cut Nuraini; Abdi Sugiarto (Equivalent : Journal of Economic, Accounting and Management, 2026)
RETRACTION NOTICE The Editorial Board of Equivalent: Journal of Economic, Accounting and Management hereby announces that the following article has been officially retracted from the journal. Article ID: 1967Title: Implications of Settlement Expansion on the Availability of Green Open Space in Medan Johor DistrictAuthors: Syarif Hidayatullah, Cut Nuraini, Abdi SugiartoPublished in: Equivalent: Journal of Economic, Accounting and Management, Vol. 4 No. 2 (2026)Article Link: https://jurnal.dokicti.org/index.php/equivalent/article/view/1967 Following an editorial investigation, it was determined that this article constitutes a duplicate publication. An identical version of the manuscript had already been published previously in the same journal, as detailed below: Article ID: 1889Title: Implications of Settlement Expansion on the Availability of Green Open Space in Medan Johor DistrictAuthors: Syarif Hidayatullah, Cut Nuraini, Abdi SugiartoArticle Link: https://jurnal.dokicti.org/index.php/equivalent/article/view/1889 The Editorial Board concluded that this situation resulted from two contributing factors: The authors submitted the same manuscript more than once (double submission), resulting in duplicate publication. The editorial office failed to identify the duplicate manuscript during the final editorial checking process prior to publication. In accordance with the journal's commitment to maintaining academic integrity, publication ethics, and the accuracy of the scholarly record, the Editorial Board has decided to retract Article ID 1967. Meanwhile, Article ID 1889 remains the valid and citable version of record, as it was the first published version of the manuscript. The Editorial Board acknowledges its responsibility for the oversight and has taken this corrective action to preserve the integrity of the journal. We sincerely apologize to our readers, authors, reviewers, indexing services, and the wider academic community for this error. To prevent similar incidents in the future, the journal will strengthen its editorial workflow by implementing more rigorous manuscript screening procedures, publication history verification, metadata validation, and final pre-publication checks. We appreciate the understanding and continued support of the academic community in upholding the highest standards of scholarly publishing.  Editorial BoardEquivalent: Journal of Economic, Accounting and Management